Investigação dos mecanismos envolvidos na herança mitocondrial: o papel da dinâmica mitocondrial - Macabelli, Carolina Habermann (2020)
Diseases caused by mutations in mitochondrial DNA (mtDNA) are the most common genetic diseases in humans. Despite this, there is no effective treatment for these diseases and the mechanisms of inheritance are not fully understood. Several studies in mice and humans have shown that deleterious mutations (e.g., non-synonymous) in mtDNA are negatively selected in the germline (e.g., oocytes or embryos) leading to a direct impact on the following generations. This mechanism seems to be closely associated with mitochondrial dynamics (e.g., mitochondrial fusion and fission events), which act on the segregation of mutant and wild-type molecules. However, there is a lack of evidence on the action of these mechanisms on mitochondrial inheritance, especially in the germline of mammals. This work aims to study the role of mitochondrial dynamics on the inheritance of mtDNA during the development of the female germline. For this, the following development phases were used as a model: i) initial embryogenesis; ii) establishment of primordial germ cells (PGCs); iii) oogenesis. Our results indicate a purifying mechanism acting on mutant mtDNA, which is dependent on Mfn2, and acts during the development of oocytes. In addition, we highlight the derivation of PGCs in Mfn2 knockout mice, and the specification of PGCLCs (PGC-like cells) from Drp1-deficient mice embryonic stem cells (mESCs), both with an effect on the mtDNA copy number. In conclusion, our results provide evidence that mitochondrial dynamics play an important role in regulating the mitochondrial inheritance.